2015
DOI: 10.1186/s13075-015-0717-z
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive IgG antibody response against mutated citrullinated vimentin predicts response to rituximab in patients with rheumatoid arthritis

Abstract: IntroductionAntibodies against mutated citrullinated vimentin (AMCV) represent a useful diagnostic marker with correlation to disease activity in patients with rheumatoid arthritis (RA). Since seropositivity for citrullinated autoantibodies was predictive for response to B-cell depleting therapy (BCDT) with rituximab (RTX), we investigated whether differences in antibody fine reactivity and immunoglobulin (Ig) isotype kinetics among AMCV-positive patients could provide additional information about outcome.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
2
0
2
Order By: Relevance
“…Это в определенной степени соответствует данным, касающимся эффектов РТМ при других ИВРЗ. Так, при системной красной волчанке лечение РТМ приводит к снижению титров антител к двуспиральной ДНК, антител к кардиолипину [39][40][41] и антител к C1q [42], а у пациентов с ревматоидным артритом (РА) -ревматоидных факторов (РФ), антител к виментину и, в меньшей степени, антител к циклическим цитруллинированным белкам (АЦЦБ) [43][44][45]. Сходные результаты в отношении динамики антинейтрофильных цитоплазматических антител продемонстрированы у пациентов с системными васкулитами [46,47], антител к базальной мембране клубочка -у пациентов с синдромеом Гудпасчера [48,49], антител к рецептору фосфолипазы А2 -у пациентов с мембранозной нефропатией [50,51], антител к тромбоцитам -у пациентов с иммунной тромбоцитопенией [52], антител к эритроцитам -у пациентов с аутоиммунной гемолитической анемией [53], антител к островковым клеткам поджелудочной железы -у пациентов с сахарным диабетом [54].…”
Section: Discussionunclassified
“…Это в определенной степени соответствует данным, касающимся эффектов РТМ при других ИВРЗ. Так, при системной красной волчанке лечение РТМ приводит к снижению титров антител к двуспиральной ДНК, антител к кардиолипину [39][40][41] и антител к C1q [42], а у пациентов с ревматоидным артритом (РА) -ревматоидных факторов (РФ), антител к виментину и, в меньшей степени, антител к циклическим цитруллинированным белкам (АЦЦБ) [43][44][45]. Сходные результаты в отношении динамики антинейтрофильных цитоплазматических антител продемонстрированы у пациентов с системными васкулитами [46,47], антител к базальной мембране клубочка -у пациентов с синдромеом Гудпасчера [48,49], антител к рецептору фосфолипазы А2 -у пациентов с мембранозной нефропатией [50,51], антител к тромбоцитам -у пациентов с иммунной тромбоцитопенией [52], антител к эритроцитам -у пациентов с аутоиммунной гемолитической анемией [53], антител к островковым клеткам поджелудочной железы -у пациентов с сахарным диабетом [54].…”
Section: Discussionunclassified
“…High titers of anti-CarbV IgM were associated with a poor response to MTX monotherapy, whereas a nonsignificant trend toward a better response with baricitinib and baricitinib plus MTX was observed. Other studies have shown that seropositive patients with RA have a better response to treatment modalities than seronegative patients [33] and that autoantibodies of the IgA subclass are predictive of a response to rituximab treatment [34]. However, patients with poor prognostic factors may still show a good response to treatment, as demonstrated in studies of patients positive for ACPA who responded to treatment with rituximab or abatacept [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…An association between anti-MCV levels and extra-articular manifestations of RA has been detected [ 48 ]. Moreover, anti-MCV seems to also be a predictive marker of the response to rituximab treatment [ 49 ]. Several antibody types have been identified only in certain subsets of RA and present a complex pattern with partial overlaps between the different antibodies.…”
Section: Serum Biomarkers In Rheumatoid Arthritismentioning
confidence: 99%